Canadian Association of Gastroenterology Practice Guidelines: Evaluation of Dysphagia - Alan W Cockeram (Canadian Journal of Gastroenterology)
Dysphagia may be defined as difficulty in swallowing. Dysphagia may be classified as oropharyngeal or esophageal; oropharyngeal dysphagia arises from a structural or functional abnormality in the oropharynx, and esophageal dysphagia occurs as a result of structural or functional abnormalities in the esophagus. Esophageal dysphagia may be further subclassified symptomatically as dysphagia for solids alone, which usually suggests a mechanical problem, versus dysphagia for liquids and solids, which is more suggestive of a neuromuscular problem. Dysphagia may be described by the patient as a sensation of food 'sticking' or as a sensation of food passing slowly through the esophagus. True dysphagia always indicates organic disease and always warrants investigation and consultation if no cause is found in initial studies. These symptoms should be distinguished from those of a persistent foreign body-type sensation or a sensation of a lump, which is more typical of globus sensation. Odynophagia, defined as pain with swallowing, may occur in association with esophageal dysmotility or as a result of mucosal disease in the esophagus.